2015
DOI: 10.1073/pnas.1509285113
|View full text |Cite
|
Sign up to set email alerts
|

Rod disc renewal occurs by evagination of the ciliary plasma membrane that makes cadherin-based contacts with the inner segment

Abstract: The outer segments of vertebrate rod photoreceptors are renewed every 10 d. Outer segment components are transported from the site of synthesis in the inner segment through the connecting cilium, followed by assembly of the highly ordered discs. Two models of assembly of discrete discs involving either successive fusion events between intracellular rhodopsin-bearing vesicles or the evagination of the plasma membrane followed by fusion of adjacent evaginations have been proposed. Here we use immuno-electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 41 publications
3
110
0
Order By: Relevance
“…This remarkable rate of membrane turnover and RPE phagocytosis is balanced by daily disc regeneration, but an understanding of the cellular process of regeneration of new photoreceptor discs has been poorly understood. Recently, new electron microscopy methodologies have revealed that OS discs are formed through a process of membrane evagination and indicate a highly regulated and ordered process at play in building photoreceptor discs (11)(12)(13). Rhodopsin is not only a photoreceptor but is a required structural component for disc membrane formation.…”
Section: Docosahexaenoic Acid (Dha)mentioning
confidence: 99%
See 1 more Smart Citation
“…This remarkable rate of membrane turnover and RPE phagocytosis is balanced by daily disc regeneration, but an understanding of the cellular process of regeneration of new photoreceptor discs has been poorly understood. Recently, new electron microscopy methodologies have revealed that OS discs are formed through a process of membrane evagination and indicate a highly regulated and ordered process at play in building photoreceptor discs (11)(12)(13). Rhodopsin is not only a photoreceptor but is a required structural component for disc membrane formation.…”
Section: Docosahexaenoic Acid (Dha)mentioning
confidence: 99%
“…The early postnatal reduction in OS length without photoreceptor cell death was a striking feature of Mfsd2a KO retinas. The OS contains photoreceptor disc membranes that form through membrane biogenesis in the IS (11)(12)(13), occurring on a daily basis to balance photoreceptor disc turnover at the distal OS via phagocytosis by the RPE (10). It can be imagined that this high level of membrane biogenesis to build OS discs would apply unique metabolic demands on the retina.…”
Section: Srebp1cmentioning
confidence: 99%
“…The Steinberg et al two-step model is well supported by studies showing that disk differentiation by rim formation (assayed by the presence of peripherin-2/rds) is always accompanied by the appearance of an enclosing plasma membrane in both rods and cones (Arikawa et al, 1992; Burgoyne et al, 2015). The addition of new plasma membrane at specific growth points (Fig.…”
Section: Photoreceptor Morphologymentioning
confidence: 88%
“…Models of disk formation by endosomal expansion (vs. plasma membrane evagination) have enjoyed limited but continued support (Chuang et al, 2007; Obata and Usukura, 1992), including a recent revival that argued for a similar “vesicular targeting” model (Sung and Chuang, 2010). A trio of recent publications have thoroughly examined the question of disk morphogenesis in numerous vertebrate species (discussed below), that together provide a compelling body of evidence that strongly upholds the plasma membrane evagination model for morphogenesis of vertebrate rod photoreceptors (Burgoyne et al, 2015; Ding et al, 2015; Pugh, 2015; Volland et al, 2015). Current thinking suggests that disk membrane morphogenesis in cones follows essentially similar principles (Mustafi et al, 2009).…”
Section: Photoreceptor Morphologymentioning
confidence: 99%
“…1). This topological inversion occurs as a result of fusion of adjacent newly formed disc membranes to form discrete discs, a fusion event visualised in tomographic series in Burgoyne et al 1 The continuity of the forming discs with the plasma membrane, together with their topology, is not consistent with the vesiculation model, which would predict that the nascent discs would be cytoplasmic vesicles, rather than exposed to the extracellular space. Consistently we did not find rhodopsin-bearing cytoplasmic vesicles in either the base of the OS or in the connecting cilium.…”
mentioning
confidence: 99%